Band inversion induced multiple electronic valleys for high thermoelectric performance of SnTe with strong lattice softening. (March 2020) - Xie, Guizhen; Li, Zhi; Luo, Tingting; Bai, Hui; Sun, Jinchang; Xiao, Yu; Zhao, Li-Dong; Wu, Jinsong; Tan, Gangjian; Tang, Xinfeng
Abstract: Band engineering has been under development as an efficient method to improve thermoelectric performance. However, except conventional methods like engineering the resonant states or band convergence, there is still no other effective way to engineer the electronic structure. Here, in this study we demonstrate a new mechanism achieved by alloying GeTe and PbTe into SnTe where multiple electronic valleys are introduced due to band inversion effect. The modification of band structure in SnTe leads to considerable enhancement of Seebeck coefficient. In the meanwhile, GeTe/PbTe coalloying leads to significant lattice softening by intense internal stains, arisen from the high density dislocations at the grain boundaries. The lattice softening leads to a low lattice thermal conductivity. In combination with Cd doping for band gap enlargement, a high thermoelectric figure of merit ZT  > 1.4 is achieved at ~873 K in the sample Sn0.48 Cd0.02 Ge0.25 Pb0.25 Te, which is doubled compared to that of pristine SnTe. It is the first example that multiple electronic valleys are introduced into SnTe system via band inversion. This new approach for band structure engineering should be equally applicable to other thermoelectric materials. Graphical abstract: Image 1 Highlights: Reconstruction of electronic band structure has been demonstrated in SnTe through band inversion. Multiple electronic valleys in SnTe contributes to high Seebeck coefficient. Strong lattice dislocations induced by GeTe and PbTe coalloying in SnTe lead to much suppressed thermal conductivity. A high ZT  > 1.4 was realized at 873 K in SnTe-based thermoelectric materials.